2020
DOI: 10.1038/s41598-020-69441-w
|View full text |Cite
|
Sign up to set email alerts
|

Elevational is the main factor controlling the soil microbial community structure in alpine tundra of the Changbai Mountain

Abstract: Different rhizosphere soil bacterial communities at similar elevations. The results of the ANOVA showed the rhizosphere soil properties of different plants at the same altitude were different significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 89 publications
(117 reference statements)
3
26
0
Order By: Relevance
“…The structure and diversity of the soil microbial community are easily affected by factors such as climate change, vegetation types, and soil properties (Liang et al, 2015 ; Tang et al, 2020 ; Tan et al, 2021 ). Previous studies showed that the soil bacterial community structure of paddy fields with different cultivation years of continuous fertilization has differentiated, and the soil bacterial community of paddy fields with 25 years of cultivation is significantly different from that of 9 and 15 years of cultivation (Li et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…The structure and diversity of the soil microbial community are easily affected by factors such as climate change, vegetation types, and soil properties (Liang et al, 2015 ; Tang et al, 2020 ; Tan et al, 2021 ). Previous studies showed that the soil bacterial community structure of paddy fields with different cultivation years of continuous fertilization has differentiated, and the soil bacterial community of paddy fields with 25 years of cultivation is significantly different from that of 9 and 15 years of cultivation (Li et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the true aspects of the environment imparting selective pressures cannot be known without further experiments. For example, suppose elevation gradients drove differences in microbial communities in Hawaiian habitats, as they do in other regions (Tang et al, 2020). Under this hypothetical scenario, differences in pathogenicity or nutritional quality of microbial communities might be the true driver of variation in selection pressure for Hawaiian C.…”
Section: The Genomic Architecture Of Local Adaptationmentioning
confidence: 99%
“…Elevational gradients have been studied to evaluate the relationships between altitude, spatial distribution patterns, and basic biome ecological processes in montane ecosystems 1 3 . Understanding how soil bacterial communities respond to particular environmental variables is of great ecological importance, and our current understanding of soil bacterial community elevational patterns in mountain grasslands remains relatively limited.…”
Section: Introductionmentioning
confidence: 99%